تصور طلاب قسم تعليم اللغة العربية لاستخدام تشاد جي بي تي (ChatGPT) في كتابة الرسالة العلمية بجامعة سلطانة نهراسية الإسلامية الحكومية لهؤسيماوي - Asyifa Nabila; Syukran; Said Alwi; Samsuar A. Rani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
This study aims to determine the perceptions of Arabic Language Education students toward the use of ChatGPT in academic writing. This research is motivated by the development of artificial intelligence technology that has begun to be used in academic contexts. The method used is descriptive quantitative with a survey approach. The subjects of this study were 30 final-year students at UIN Sultanah Nahrasiyah Lhokseumawe. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. The results showed that students’ perceptions of ChatGPT use were in the high category, with a mean score of 3.24 or approximately 81%. Students showed positive attitudes toward the use of ChatGPT, especially in generating ideas and constructing sentences. In addition, students were able to evaluate its use critically, such as recognizing the importance of verifying information. Therefore, ChatGPT can be considered a learning innovation that supports academic writing, provided that it is used wisely and with academic responsibility.